2017
DOI: 10.17576/jsm-2017-4608-18
|View full text |Cite
|
Sign up to set email alerts
|

Response of LiF: Mg, Cu, P TL Detector Simulated with Geant4

Abstract: The Geant4 simulation code was developed to study the H p (10) energy response of the LiF:Mg,Cu,P (TLD-100H). Initial study chose the simulation conditions similar to the work reported by Obryk et al. in year 2011, in which a TLD-100H chip without filter was used. The work went further to simulate the H p (10) results obtained experimentally at SSDL Malaysia. The experiment used a TLD-100H chip embedded in a TLD card and the card was enclosed in a badge complete with PTFE filter. Irradiation with eleven photon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The lowest deviation value with a minimum computational time was yielded when 2×10 9 number of events were selected. From this number upwards, both the deviation value and the computational time keep increasing until the maximum number of events that can be handled by the CPU (2×10 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest deviation value with a minimum computational time was yielded when 2×10 9 number of events were selected. From this number upwards, both the deviation value and the computational time keep increasing until the maximum number of events that can be handled by the CPU (2×10 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, based on previous studies, it was reported that a flat energy response, especially for TLD: LiF: Mg, Cu, P can only be achieved at high energy (> 500 keV). Whereas at low energy (<500 keV), this has not been materialized [10][11] [12].…”
Section: Introductionmentioning
confidence: 99%